Caring for solidarity? The intimate politics of grandmother childcare and neoliberal conservatism in urban Turkey. (May 2019) - Can, Başak
Abstract: The number of grandmothers who provide regular care for their grandchildren and do housework for their daughters or daughters-in-law is increasing in Turkey. While perpetuating traditional gender roles for themselves as a surrogate daughter, wife, or daughter-in-law, these women nonetheless enable younger women to distance themselves from obligatory care work at home. The sociocultural concepts of kinship ties, economic need, or love for grandchildren do not fully explain why grandmothers assume the role of caregiver for their grandchildren. Drawing on interviews with 25 grandmothers from middle-class families in urban Turkey, this article shows, first, that these women's gendered subjectivity is formed by both habitual and intentional actions that defying the oppression and resistance duality within patriarchal Turkish society. Second, in dialogue with the scholarship on the "classic patriarchal bargain" 1 and feminist analyses of neoliberal social policy, the article suggests that these grandmothers' inarticulate desire to live in solidarity with the younger generation of women may be turned into a government instrument in the context of Turkey's increasingly family-centered neoliberal social policy environment.